Preliminary Estimates of Diaspora Savings - Ratha, Dilip; Mohapatra, Sanket (World Bank, Washington, DC, 2012)
Preliminary estimates, based on data on bilateral migrant stocks for 2010 and assumptions about migrant incomes, suggest that annual diaspora savings of developing countries could be in the range of $400 billion. Diaspora saving as a share of Gross Domestic Product (GDP) is estimated to be 2.3 percent in middle-income countries and as high as 9 percent in low-income countries.